2011
DOI: 10.1089/hyb.2011.0038
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody for in vivo Detection of Peroxisome-associated PTS1 Receptor

Abstract: PEX5 is a key protein of the peroxisomal protein import machinery. This cycling receptor binds newly synthesized proteins with a peroxisomal targeting signal type 1 in the cytosol and directs them to the peroxisomal membrane. There, PEX5, together with its docking protein, forms a transient membrane-spanning channel that enables cargo-transport across the membrane. Through interaction with other multimeric membrane complexes, the receptor is released from the membrane back to the cytosol. Very little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…At the membrane, PEX5 is interacting with PEX14, triggering the translocation of the cargo protein [15–17] . The monoclonal PEX5 antibody used here, only binds to PEX5 when it is located at the peroxisomal membrane and not to the cytosolic pool of the shuttling receptor [18] . Here, we obtained good STED images using PEX14 and PEX5 in a dual colour STED colocalization study [8] but the signal with the PEX5 antibody was too weak for ExM‐STED (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…At the membrane, PEX5 is interacting with PEX14, triggering the translocation of the cargo protein [15–17] . The monoclonal PEX5 antibody used here, only binds to PEX5 when it is located at the peroxisomal membrane and not to the cytosolic pool of the shuttling receptor [18] . Here, we obtained good STED images using PEX14 and PEX5 in a dual colour STED colocalization study [8] but the signal with the PEX5 antibody was too weak for ExM‐STED (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…1 A ). For studying membrane-bound PEX5, only an antibody specifically recognizing the membrane-bound conformation ( 17 ) was used.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were incubated with primary antibodies in blocking buffer for 1 h at room temperature. To stain peroxisomal proteins, antibodies recognizing PEX14 ( 38 ), PEX5 ( 17 ), and PEX11B (Abcam, Cambridge, UK) were used. Mitochondria were visualized using an antibody against TOM20 (FL-145, Santa Cruz Biotechnology, Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…To study interactions between PEX5 and PEX13 dynabeads were coupled with a mouse PEX5 antibody 65 , using the dynabeads™ Antibody Coupling Kit (Invitrogen, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%